Partitioning the relative fitness effects of diet and trophic morphology in the threespine stickleback - Bolnick, Daniel I.; Araújo, Márcio S. [UNESP] (My University, 2011)
Background: Numerous models show that if morphology and diet are correlated, frequencydependent competition will lead to fitness differences among phenotypically dissimilar individuals within a species. Hypothesis: Selection acts primarily on diet, and only indirectly on morphology via its correlation with diet. Field sites and organism: British Columbia, Canada; 340 individual threespine stickleback (Gasterosteus aculeatus) from McNair Lake and 430 individuals from First Lake. Measurements: Stable isotopes (δ 13C and δ 15N; a proxy for diet); trophic morphology (quantitative traits and geometric shape variables); and growth rates (RNA/DNA ratios; a proxy for the component of fitness arising from competitive or foraging ability). Analysis: Linear and quadratic regression of growth rate on stable isotopes and morphological variables to calculate the relationship between growth (a fitness proxy) and diet and/or morphology. When both morphology and isotopes affected growth rates, we used a path analysis to separate their effects. Conclusions: In the McNair Lake population, growth was dependent primarily on diet type and only indirectly on trophic morphology. In a second population, path analysis found that isotopes and body shape separately explain variation in growth rates. We infer that, in stickleback, selection on trophic morphology is often a correlated side-effect of selection on diet composition, rather than direct fitness effects of morphology per se. © 2011.
Keywords: Directional selection; Fitness landscape; Frequency-dependent selection; Function-valued trait; Gasterosteus aculeatus; Stabilizing selection; Stable isotopes; Trophic morphology